Effect of transforming growth factor- beta 1 on interleukin-6 secretion in human myoblasts - Mazzarelli, P; Scuderi, F; Mistretta, G; Provenzano, C; Bartoccioni, E (Journal of neuroimmunology, 1998)
Transforming growth factor- beta (TGF- beta ) is involved in several autoimmune neurological diseases. It is still unclear whether its local action can be pro-inflammatory or anti-inflammatory in the muscle tissue, because of the few reports on this subject. We have previously shown that human myoblasts secrete interleukin-6 (IL-6) when stimulated with inflammatory cytokine such as interleukin-1 beta (IL-1 beta ) or tumor necrosis factor alpha . In the present report, we show that TGF- beta 1 can induce IL-6 production; moreover, costimulation or short term pre-incubation with TGF- beta 1 increases IL-1 beta effect, while a longer incubation inhibits its action.